Differential Kinetics of Coagulation Factors and Natural Anticoagulants in Patients with Liver Cirrhosis: Potential Clinical Implications - Tischendorf, Michael (PLoS One, 2016)
BACKGROUND: Advanced liver diseases are associated with profound alterations of the coagulation system increasing the risk not only of bleeding, but also of thromboembolic complications. A recent milestone study has shown that prophylactic anticoagulation in liver cirrhosis patients results in a reduced frequency of hepatic decompensation. Yet, INR measurement, one of the most widely applied tests to assess liver function, only inaccurately predicts the risk of hepatic decompensation related to alterations of the coagulation system. To assess the relationship between selected coagulation factors / natural anticoagulants with INR, MELD score, and hepatic decompensation, we performed the present pilot study. A total number of 92 patients with various stages of liver cirrhosis were included and prospectively followed for at least 6 months. We found that important natural anticoagulants, namely antithrombin and protein C, as well as factor XI (which may also serve as an anticoagulant) decreased earlier and by a larger magnitude than one would expect from classical coagulation test results. The correlation between these factors and INR was only moderate. Importantly, reduced plasma activities of natural anticoagulants but not INR or MELD score were independent predictors of hepatic encephalopathy (P = 0.013 and 0.003 for antithrombin and protein C, respectively). CONCLUSION: In patients with liver cirrhosis plasma activities of several natural anticoagulants are earlier and stronger affected than routine coagulation tests. Reduced activities of natural anticoagulants may be predictive for the development of hepatic encephalopathy.